2015
DOI: 10.1111/hpb.12332
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous needle aspiration versus catheter drainage in the management of liver abscess: a systematic review and meta-analysis

Abstract: Both PNA and PCD are safe methods of draining liver abscesses. However, PCD is more effective than PNA because it facilitates a higher success rate, reduces the time required to achieve clinical relief and supports a 50% reduction in abscess cavity size. However, among successfully treated patients, the outcomes of PNA are comparable with those of PCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 25 publications
6
105
0
6
Order By: Relevance
“…A meta-analysis comparing catheter drainage vs. repeated needle aspirations of liver abscesses demonstrated the first to be more effective [27]. Other studies showed good results with repeated needle aspiration in simple abscesses smaller than 5 cm, while in larger abscesses catheter drainage has a better outcome [26].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis comparing catheter drainage vs. repeated needle aspirations of liver abscesses demonstrated the first to be more effective [27]. Other studies showed good results with repeated needle aspiration in simple abscesses smaller than 5 cm, while in larger abscesses catheter drainage has a better outcome [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, greater age (≥ 55 years), presence of multiple abscesses, malignancy as etiology, and endoscopic intervention were reported to be the risk factors for the development of PLA treatment failure with antibiotics alone [24]. In our cohort, 50 % of MPLPs were larger than 5 cm in diameter and 29 % were multiple.…”
Section: Discussionmentioning
confidence: 68%
“…The antibiotic treatment was optimized afterward according to the results of the bacterial cultures and antimicrobial susceptibility analysis of the isolated pathogens. Patients with abscesses larger than 3 cm in diameter predominantly underwent source control by PCD with 7 Fr catheter drainage within 24 hours, except in the following situations: (a) when the lesions were MPLPs, and (b) when there was a safety concern about PCD such as bleeding tendencies and a moderate-high amount of ascites [13,14,24]. The duration of drainage catheter placement ranged from 4 to 10 days.…”
Section: Principal Treatment Strategies For Plamentioning
confidence: 99%
“…Theoretically, mini-invasive procedures including final needle aspiration and persistent catheter drainage will be performed successfully for most of PLA in the nature status [12]. However, the drainage often fails in early stage of PLA because little free fluid found in imaging graphy.…”
Section: Discussionmentioning
confidence: 99%